2020
DOI: 10.1088/1757-899x/896/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Stress-strain state of wooden beams with external reinforcement

Abstract: The stress-strain state of wood-composite beams was studied numerically. Numerical studies were performed on wood-composite floor beams with a cross-section size of 100×240 mm and a length of 4.8 m. it was Experimentally proved that the deformability of wood-glued beams is reduced by 1.8…2.1 times, compared to conventional wooden beams. For wooden beams in the elastic design stage, the limiter is the calculation of the 2nd group of limit States (for stiffness), for composite beams, the calculation of the 1st g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Inspired by the natural bamboo structures with high stiffness and stability when subjected to lateral loads, Zhang et al [28] conducted flexural tests on a combined structure with hollow sections and internal stiffener ribs. Lukin et al [29] numerically analyzed the characteristics of wood composite floor beams. The results revealed that compared to the conventional wooden beams, the deformation capacity of glued laminated beams was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the natural bamboo structures with high stiffness and stability when subjected to lateral loads, Zhang et al [28] conducted flexural tests on a combined structure with hollow sections and internal stiffener ribs. Lukin et al [29] numerically analyzed the characteristics of wood composite floor beams. The results revealed that compared to the conventional wooden beams, the deformation capacity of glued laminated beams was reduced.…”
Section: Introductionmentioning
confidence: 99%